Analisis Atribut Seismik untuk Identifikasi Potensi Hidrokarbon - Maulana Hadi, Johan; Nurwidyanto, M. Irham; Yulianto, Gatot (BERKALA FISIKA, 2006)
Rms amplitude and spectral decomposition attribute have been extracted for hydrocarbon potential identification in Amandah area, Talangakar Formation, North West Java Basin. Purpose of rms amplitude extractions is to see the change of lithology which is extreme. Example is like reservoir existence. Spectral decomposition has been used to see reservoir at thin thickness. The seismic attributes has been extracted from seismic data 3D Pre Stack Time Migration (PSTM). Log data has been taken from a well (AMD-01) to interpret and determine reservoir thickness in interest zone. Seismic attribute analysis has been used to see existence and shape of channel’s geometry spreading. The result of rms amplitude attribute extraction is reservoir which can be detected clearly at 10 ms, 20 ms, 30 ms and 40 ms window analysis. Whereas the result of spectral decomposition attribute extraction is reservoir which can be detected at 15 Hz – 25 Hz frequency with 30 ms and 40 ms window analysis. The result of rms amplitude and spectral decomposition attribute analysis shows hydrocarbon in Amandah area, Talangakar Formation is potential in channel depositional facies with depositional direction at north-south (N-S) and north nort east – south south west (NNE-SSW) and thickness high of channel is concern at 36-60 m. Key words: Seismic attribute, rms amplitude, spectral decomposition, reservoir,